2017
DOI: 10.1177/1368430217709536
|View full text |Cite
|
Sign up to set email alerts
|

Twenty years of group processes and intergroup relations research: A review of past progress and future prospects

Abstract: The 20th anniversary of Group Processes & Intergroup Relations offers an opportunity to reflect on progress in research. We describe the changing context of research and the scope and progress in the field. This special issue includes reviews by distinguished scholars in the areas of social identity, ideology, crowds, intergroup contact, crossed and multiple social categorization, communication, majority–minority conflict, group-based emotion, group decision making, group performance, ostracism, and social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Theoretical research has highlighted the importance of expanding the body of research on ostracism from interindividual level to intergroup level (Abrams & Hogg, 2017; Betts & Hinsz, 2013; Wesselmann & Williams, 2017). Across three studies, we investigated the psychological impact of ostracism when participants shared this experience with someone else, particularly an ingroup member.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical research has highlighted the importance of expanding the body of research on ostracism from interindividual level to intergroup level (Abrams & Hogg, 2017; Betts & Hinsz, 2013; Wesselmann & Williams, 2017). Across three studies, we investigated the psychological impact of ostracism when participants shared this experience with someone else, particularly an ingroup member.…”
Section: Discussionmentioning
confidence: 99%
“…2,4 Consequently, social psychologists have called for research into intergroup relations that takes into account the increasing complexity of such relations. 2,4,5 Drawing on social psychologists' work on intergroup relations as they pertain to social identities may provide a deeper understanding of the mechanisms that lead to bias and can help medical educators in their efforts to promote equitable learning environments for all.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as our societies become more diverse, individuals identify with a growing number of groups, which increases the complexity of intergroup relations 2,4 . Consequently, social psychologists have called for research into intergroup relations that takes into account the increasing complexity of such relations 2,4,5 …”
Section: Introductionmentioning
confidence: 99%
“…Mastandrea et al (2021) manipulated the framing of an artwork using national identity, and proposed a novel social psychological perspective, drawing on social identity theory (Abrams & Hogg, 2017). They suggested that for people who are unfamiliar with a specific type of art may experience self-related uncertainty which might encourage the use of national identity as an art appreciation heuristic.…”
mentioning
confidence: 99%